Collaborative Learning in Virtual Learning Environments: Supporting High Quality Educational Interaction [linked with the Community Task Force, i.e. CHALCS] - Barker, Tim (Proceedings of the International Conference on Networked Learning, 1998)
The Chapeltown and Harehills district of Leeds faces many of the problems often associated with inner-city ethnic minority areas; notably, poor housing, single parents and high unemployment. These social problems arc also accompanied by high levels of truancy, drug abuse and crime. High disaffection and low expectation can further undermine educational goals and individual achievements. Chapeltown and Harehills Assisted Learning Computer School (CHALCS) was established in 1987 to address these problems by providing community-based tuition out of school hours. CHALCS currently provides support in Maths, English, Science and Information Technology.